1991
DOI: 10.1128/iai.59.5.1785-1789.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous cryptococcosis in athymic and beige-athymic mice

Abstract: The dermotropism of Cryptococcus neoformans SLHA in congenitally athymic (nu/nu) and doubly immunodeficient beige-athymic (bg/bg-nulnu) mice is described. Both bg/bg-nulnu and nulnu mice developed cutaneous cryptococcosis within 7 to 12 days following intravenous challenge with 104 encapsulated yeast cells. Macroscopically, cutaneous lesions appeared as small subcutaneous nodules without ulceration. Cryptococcal skin lesions were observed primarily on the flank of nu/nu mice, whereas skin lesions in bg/bg-nuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Collagen fibril and extracellular matrix degradation has been observed in experimental murine cryptococcal infections (34). These in vivo observations are suggestive of and consistent with the elaboration of tissue-degrading enzymes, such as extracellular proteinases, by C. neoformans (12,34). In this article, we report C. neoformans extracellular proteinase activity and demonstrate that this fungus can grow in the presence of immunoglobulin or complement proteins as the sole sources of carbon and nitrogen.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Collagen fibril and extracellular matrix degradation has been observed in experimental murine cryptococcal infections (34). These in vivo observations are suggestive of and consistent with the elaboration of tissue-degrading enzymes, such as extracellular proteinases, by C. neoformans (12,34). In this article, we report C. neoformans extracellular proteinase activity and demonstrate that this fungus can grow in the presence of immunoglobulin or complement proteins as the sole sources of carbon and nitrogen.…”
Section: Discussionsupporting
confidence: 79%
“…Rapid tissue invasion by C. neoformans has been observed in experimental rat pulmonary infections (12). Collagen fibril and extracellular matrix degradation has been observed in experimental murine cryptococcal infections (34). These in vivo observations are suggestive of and consistent with the elaboration of tissue-degrading enzymes, such as extracellular proteinases, by C. neoformans (12,34).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Generally, proteinase activity also appears to be important during C. neoformans infection, since degradation of extracellular matrix and collagen has been observed in murine infection models and is viewed as a facilitator for establishing infections in the central nervous system via permeabilization of epithelial barriers [71][72][73]. Further, C. neoformans produces several secreted proteases involved in the utilization of immunoglobulin and complement proteins as the sole nitrogen and carbon source in vitro [74].…”
Section: Utilization and Uptake Of Amino Acids And Oligopeptides In Tmentioning
confidence: 99%
“…neoformans infection commonly acquires from the environment 12 , the mechanism includes tissue invasion and is disseminated to other organs via the bloodstream from the lung [13][14][15] . Studies of experimental infection in rats suggested C. neoformans produces tissue disrupting substances such as proteolytic enzymes through which it can penetrate the lung parenchyma and histopathological studies suggested in-vivo protease production which degrades collagen fibrils in infected tissues 16 .…”
Section: Introductionmentioning
confidence: 99%